For those of you who have done Euclid's algorithm you could try:
Prove that gcd (2a-1, 2b-1) = 2gcd(a,b)-1
[Isnt the result beautiful?!]
-
UP 0 DOWN 0 0 2
2 Answers
Lokesh Verma
·2009-07-23 23:29:47
hmm.. no one?!
Lets take some example to understand why the result is beautiful
(28-1) = 255
24-1 = 15
The GCD should be 24-1
255=15x17
hence the GCD is 15...
rahul1993 Duggal
·2009-07-31 08:38:42
not a very strong proof (there may be a stronger one):
assuming b>a
so b=na+r
gcd(2a-1,2b-1)=gcd(2^a-1,2^{an+r}-1) r<a
=gcd(2a-1,[2an-1+1]2r-1)
as 2a-1 divides 2an-1,
gcd(2a-1,[(2an-1)+1]2r-1)=gcd(2a-1,2r-1)
proceeding as above we will reach a stage when
gcd(2a-1,2b-1)=gcd(20-1,2gcd(a,b)-1)=2gcd(a,b)-1
sorry i couldnt latex the solution as i'm out of station